1991
DOI: 10.1159/000282176
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of DNA Ploidy and Proliferative Activity in Urothelial Carcinoma of the Renal Pelvis and Ureter

Abstract: In 55 patients with urothelial carcinoma of the renal pelvis or ureter, the ploidy, the DNA heterogeneity and the counts of cell cycle phases in the tumor were examined by means of single-cell DNA cytophotometry in order to find more prognostic factors than those already known (stage and grade). Follow-up periods ranged from 1 to 6 years. At the time of first diagnosis, 42 (76%) of the patients had tumors of the renal pelvis, 13 (24%) of them had ureteral tumors. 23 (42%) patients were in stage pT 1 N 0, 15 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Numerous DNA analyses showed that grade I transitional cell carcinomas are predominantly diploid and grade III carcinomas are almost exclusively aneuploid. Approximately 30%-40% of grade II carcinomas are diploid and 60%-70% are aneuploid or polyploid [3,16]. The heterogeneous nature of the grade II group was also demonstrated with respect to nuclear size and DNA pattern [7,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous DNA analyses showed that grade I transitional cell carcinomas are predominantly diploid and grade III carcinomas are almost exclusively aneuploid. Approximately 30%-40% of grade II carcinomas are diploid and 60%-70% are aneuploid or polyploid [3,16]. The heterogeneous nature of the grade II group was also demonstrated with respect to nuclear size and DNA pattern [7,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognosis of carcinomas with limited invasion and intermediate differentiation showing mixed papillary/solid growth pattern is difficult to predict. Various methods assessing cell proliferation such as thymidine autoradiography, DNA-cytometry and immunohistochemical proliferation assays have been used to subgrade this group of bladder tumours [1,2,3,12,26]. The results of these studies were promising, but there is still a need for simple measures to predict the prognosis of the intermediate group of bladder carcinomas.…”
Section: Introductionmentioning
confidence: 99%